Shortage of storage carbohydrates mainly determines seed abscission in Torreya grandis ‘Merrillii’ - Tao Liu; Xiaolong Zhao; Guangxia Zhu; Caoliang Jin; Jingwei Yan; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Jiasheng Wu (Horticultural Plant Journal)
Torreya grandis ‘Merrillii’ is a well-known nut in South China with high nutritional value. Severe premature seed abscission limits the industrial development of T. grandis by causing serious economic losses. However, the physiological mechanisms of seed abscission in T. grandis remain poorly understood. To gain insight into the relationships between carbohydrate status and seed abscission, three-year-old seed-bearing branches were taken as representative materials for the entire tree. Furthermore, the time course of changes in the photosynthetic rate and the non-structural carbohydrate (NSC) dynamics were monitored in the main sources (the one-year-old and two-year-old shoots), and the dry weight and NSC levels of sinks (the seeds, current female cone cluster, and current vegetative cluster) across all seed development stages were recorded. The cumulative seed abscission rate significantly increased, reaching 91.5% from 0 to 72 days after seed protrusion time (SPT). NSC levels in the main sources significantly decreased by 56%–79%, accompanied by a significantly increased photosynthesis rate of 17.1%–49.1% during that period and increased NSC levels in the three sinks. The gene expression level of cell wall invertase (TgCWIN) was significantly correlated with sucrose, fructose, and glucose levels. The carbon storage capacity of the main sources significantly decreased from 6.03 to 3.14 mmol C · d−1, with a stable photosynthetic capacity, from 0 to 72 days after SPT, whereas the carbon demand of the three sinks showed a continuously increasing trend from 3.14 to 7.71 mmol C · d−1. In addition, sucrose supplementation significantly decreased the cumulative seed abscission rate. These results suggest that storage carbohydrates play a major role in the regulatory mechanism of seed abscission in T. grandis. Our study provides a theoretical basis for improving T. grandis yield through establishing a better carbon balance between sources and sinks using timely fertilization or proper pruning procedures.